2010
DOI: 10.2165/11536170-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The State of Health Economic Evaluation Research in Nigeria

Abstract: This study assessed the state of health economic evaluation (including pharmacoeconomic) research in Nigeria. A literature search was conducted to identify health economic articles pertaining to Nigeria. Two reviewers independently scored each article in the final sample using a data collection form designed for the study. A total of 44 studies investigating a wide variety of diseases were included in the review. These articles were published in 34 different journals, mostly based outside of Nigeria, between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
7
22
2
Order By: Relevance
“…Some areas which need significant attention of the researchers are focus of the viewpoint of the evaluations being undertaken, justification on the type of economic evaluation being used, lack of use of discount rates, weak costing methodologies and the extent to which these studies address the uncertainties in methodologies of economic evaluation, especially for model-based evaluations. Overall, our findings on quality of evidence are again very similar to what others have reported in the developing countries [125][126][127][128]. However, the overall quality in India seems better than what is reported for most of other developing countries.…”
Section: Quality Of Economic Evaluation Studies In Indiasupporting
confidence: 89%
See 1 more Smart Citation
“…Some areas which need significant attention of the researchers are focus of the viewpoint of the evaluations being undertaken, justification on the type of economic evaluation being used, lack of use of discount rates, weak costing methodologies and the extent to which these studies address the uncertainties in methodologies of economic evaluation, especially for model-based evaluations. Overall, our findings on quality of evidence are again very similar to what others have reported in the developing countries [125][126][127][128]. However, the overall quality in India seems better than what is reported for most of other developing countries.…”
Section: Quality Of Economic Evaluation Studies In Indiasupporting
confidence: 89%
“…The 104 papers included in this review compares to 1249 papers on cost effectiveness published in the USA between 1979 and 1990, and 1167 published between 1991 and 1996 [123]. Nevertheless, this exceeds the number of economic evaluation studies we found when using the same inclusion criteria in relation to other developing countries such as South Africa (n = 45), Thailand (n = 39), Vietnam (n = 26), Bangladesh (n = 12), Nigeria (n = 44) and Zimbabwe (n = 26) [124][125][126][127][128][129]. However, the gap in current economic evidence in India is exacerbated by the need for region-or state-specific studies that account for variations in epidemiological transition, health-care costs, and health-care infrastructure across the country.…”
Section: Extent Of Economic Evaluations For Health Care In Indiamentioning
confidence: 99%
“…The findings showed that the number of economic evaluation studies in Iran is limited. This is comparable with settings such as Bangladesh [60], Nigeria [26], Saudi Arabia [61], Zimbabwe [62], and lagging behind countries such as Thailand [29], South Korea [24], India [63] and South Africa [64]. The number of available studies remains very low compared with high-income countries where economic evaluation is a relatively well-established and formal part of the policy making process [21,65].…”
Section: Discussionsupporting
confidence: 74%
“…Systematic reviews of economic evaluation studies in some other settings (both developed and developing countries) have reported similar shortcomings [21,23,24,26,29,60-65]. For this reason, many countries have developed formal and informal guidelines to standardize and improve the quality of economic evaluation in health care [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation